A History and Methodology of Research of the Subnational Topic in Political Science - Hnatiuk, Volodymyr Viktorovych (Politologija, 2019)
Subnational topic has come a long way from its inception fifty years ago to formation of an independent research direction. This period consists of three phases. In the first phase (early 1970’s – mid 90’s) scholars start discussing a topic that was still unexplored at the time and examine it as a fragmentary part of whole studies. The second phase (mid 1990’s – first half of 2010’s) sees changes in methodology: studies become more complex, focused solely on subnational phenomena and are carried out using a special tool – the subnational comparative method. A methodological dichotomy is outlined as a model for the analysis of subnational regimes and their types, as well. Finally, the third (current) phase (mid 2010’s – present) is where the key changes take place: formation of independent research direction, overcoming theoretical constructs (whole-national bias and federal monism) and increase of complexity and depth of political studies. These features are entrenched in the form of methodological synthesis as a modern model for the analysis of subnational regimes and their types. The article focuses on the coverage of the classical and the modern foundations of the subnational comparative method. The author notes that modern methodology juxtaposes with ontology in the context of subnational discourse. However, in the process of studying such issues there is an urgent need to clarify, update and supplement some methodological foundations of the method.
Keywords: subnational topic; subnational regime; subnational comparative method; methodological dichotomy; methodological synthesis; objective and subjective measurements